Impact of pre-treatment with pulsed electric field on drying rate and changes in spinach quality during hot air drying. (March 2021) - Yamakage, Koya; Yamada, Takahiro; Takahashi, Katsuyuki; Takaki, Koichi; Komuro, Misaki; Sasaki, Kuniaki; Aoki, Hitoshi; Kamagata, Junichi; Koide, Shoji; Orikasa, Takahiro
Abstract: This study aimed to compare the impact of a pulsed electric field (PEF) with that of hot water (HW) and control (CONT) on subsequent drying rate, shrinkage, and quality parameters (degradation of l -ascorbic acid (L-AsA) and color) of spinach during hot air drying. PEF pre-treatment was conducted in 2.8 kV/cm of the electric field strength and 27.1 kJ/kg of the specific input energy. We found that the drying rate for PEF sample was increased compared with CONT and HW samples due to the inhibition of shrinkage during drying. Further, degradation of L-AsA and the surface color in PEF sample were significantly inhibited compared with HW sample, therefore we confirmed that PEF treatment could resolve the elution of water-soluble components caused by HW treatment. These findings showed that pre-treatment with PEF is suitable for reducing drying time and producing high-quality dried spinach. Highlights: Pulsed electric field was applied to drying of spinach as a pre-treatment. The drying rate of treated samples increased in an early stage of drying. Quality changes were inhibited compared with hot water pre-treatment. The pulsed electric field treatment would contribute to produce high quality dried products.